1996
DOI: 10.1007/s004670050218
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoureteral reflux: practical aspects of evaluation and management

Abstract: The efficacy of both medical and surgical therapy for vesicoureteral reflux (VUR) has been well established. Controversy remains, however, regarding who should be evaluated for the presence of VUR, who should undergo corrective surgery, who should be treated medically and for how long. Medical treatment requires many years of continuous antibiotic prophylaxis, so compliance with therapy is essential. Many children are lost to followup, however, and remain untreated after a medical regimen is started. This larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 50 publications
(61 reference statements)
0
42
0
4
Order By: Relevance
“…But they failed to show any document and no prenatal diagnosis was done in any patient in present study. Greenfield & Wan (1996) showed that reflux is the most common underlying cause of antenatally detected hydronephrosis 15 . The advantage of identifying children antenatally is that treatment, either prophylaxis or surgery, can be instituted early and further scarring can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…But they failed to show any document and no prenatal diagnosis was done in any patient in present study. Greenfield & Wan (1996) showed that reflux is the most common underlying cause of antenatally detected hydronephrosis 15 . The advantage of identifying children antenatally is that treatment, either prophylaxis or surgery, can be instituted early and further scarring can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, pediatric urologists have learned to be more and more conservative in treating VUR [12]. Evidence suggests that low-grade VURs usually cease spontaneously over time, whereas renal damage is mostly congenital in children with high-grade VUR undergoing renal function deterioration while on conservative treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, outcome is largely independent from surgery [14] and a nonoperative treatment has become the first-line approach to VUR, no matter what grade or laterality [1,[12][13][14][15]. Surgery seems indicated only on a clinical ground, potential indications for reimplantation being breakthrough UTIs, appearance of new renal scars or worsening in renal function during follow-up, and parents' noncompliance with long-term prophylaxis [1,12]. Accordingly, accuracy of the imaging modality in grading VUR seems no longer paramount.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations